Assessment on Internal Audit Capability Level in a Public Sector Organisation Case Study on a Local Government - Aireen Mak, Siew Fern; Hasnah, Haron; Ishak, Ismail; Yuvaraj, Ganesan; Fathyah, Hashim (Jabatan Audit Negara Malaysia, 2016)
Internal auditing has become an important function in assisting the public sector organisation in achieving its objectives efficiently. This study serves to explore the level of capability of Internal Audit (IA) in a government agency in the public sector of Malaysia. Internal Audit Capability Model (IACM) from the Institute of Internal Audit Research Foundation was used as a basis to assess the capability level of IA. A series of interviews were conducted with the Ministry of Finance, Prime Minister’s Department, Penang State Audit Department and IA department from a local government to better understand the public sector’s structure, performance measurement systems and applicability of IACM in the public sector. IACM evaluation shows a strong establishment in elements of Services and Role of IA and Organisational Relationships and Culture, scoring a capability level of 4 or 5. There is a need to review the remaining elements (People Management, Professional Practices, Performance Management and Accountability, and Governance Structure which were evaluated at capability level 2 or 3 to enhance the effectiveness of the IA function in the related government agency. The IACM model could be a centralize assessment to serve as a common communication vehicle within the country as well as globally. Implications and suggestions for further studies are also provided in this study.